Representations of Gender in Belloc Lowndes' The Lodger - Berná, Jana (Univerzita Pardubice, 2017)
This bachelor thesis focuses on the life of Victorian women, gender roles, and stereotypes and shows them on the example of two heroines from books The Lodger by Marie Belloc Lowndes and Jane Eyre by Charlotte Brontë. The first part of the paper deals with patriarchal concept and its influence on the everyday life of people. The difference between lives of men and women are presented. It also focuses on gender stereotypes and phenomena of The Angel in the House and The New Woman. The second part of the paper deals with finding these phenomena in the books mentioned above and description of the two female heroines from these books.
Ztvárnění pohlaví v knize The Lodger od Marie Belloc Lowndes
Keywords: Nová žena; Anděl v domě; Viktoriánská Anglie; genderové stereotypy; Jana Eyrová; Příšerný host/Podnájemník; The New Woman; The Angel in the House; Victorian England; and gender stereotypes; Jane Eyre; The Lodger